Filtration process cost in submerged anaerobic membrane bioreactors (AnMBRs) for urban wastewater treatment. Issue 3 (11th February 2016) - Pretel, R.; Robles, A.; Ruano, M. V.; Seco, A.; Ferrer, J.
ABSTRACT: The objective of this study was to evaluate the effect of the main factors affecting the cost of the filtration process in submerged anaerobic membrane bioreactors (AnMBRs) for urban wastewater (UWW) treatment. Experimental data for CAPEX / OPEX calculations was obtained in an AnMBR system featuring industrial-scale hollow-fiber (HF) membranes. Results showed that operating at J20 slightly higher than the critical flux results in minimum CAPEX / OPEX . The minimum filtration process cost ranged from €0.03 to €0.12 per m 3, mainly depending on SGDm (from 0.05 to 0.3 m 3 ·m −2 ·h −1 ) and MLSS (from 5 to 25 g·L −1 ). The optimal SGDm resulted in approx. 0.1 m 3 ·m −2 ·h −1 .